Retos actuales de las empresas japonesas - Umezu, Hiroyoshi (1999)
Information technologies and telecommunications are advancing at high speed consequently the companies that maintain valuable information today will be the winners in this competitive global market. Japanese companies mainly banks financial institutions and high-tech industries need to improve their ability to acquire valuable information in order to compete in the global market.